2022
DOI: 10.1503/jpn.210124
|View full text |Cite
|
Sign up to set email alerts
|

The functional and structural associations of aberrant microglial activity in major depressive disorder

Abstract: Background: Major depressive disorder (MDD) is a debilitating mental illness that has been linked to increases in markers of inflammation, as well as to changes in brain functional and structural connectivity, particularly between the insula and the subgenual anterior cingulate cortex (sgACC). In this study, we directly related inflammation and dysconnectivity in treatment-resistant MDD by concurrently measuring the following: microglial activity with [ 18 F]N-2-(fluoroethoxyl)benzyl-N-(4phenoxypyridin-3-yl)ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 93 publications
(115 reference statements)
0
6
0
Order By: Relevance
“…It is suggested that microglial overactivity is related to poor response, longer disease duration, and increased inflammatory response [ 43 ]. A recent preliminary study combined PET and magnetic resonance imaging (MRI) and found a connection between disturbed connectivity and increased microglial activity in MDD [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that microglial overactivity is related to poor response, longer disease duration, and increased inflammatory response [ 43 ]. A recent preliminary study combined PET and magnetic resonance imaging (MRI) and found a connection between disturbed connectivity and increased microglial activity in MDD [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…A significant decrease in 3-HK levels was observed in the serum of schizophrenic patients [ 82 ]. Thus, these diseases may be associated with microglial activation [ 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, many studies have also demonstrated that changes in the gut microbiota trigger inflammatory cytokines, such as IL-6, IL-1β, IL-2, and IFN-γ. These cytokines can reach the brain through neuroanatomical and neuroendocrine pathways, thus affecting mental health and behavior [ 14 , 15 , 16 , 17 , 45 ].…”
Section: Neurobiology Of Major Depressive Disordermentioning
confidence: 99%
“…Moreover, patients treated with cytokines such as IL-2 and interferon-γ (IFN-γ) for viral infections or cancer may develop depressive symptoms [ 15 ]. Additionally, individuals with autoimmune and chronic inflammatory diseases, including rheumatoid arthritis, multiple sclerosis, fibromyalgia, and inflammatory bowel disease are likely to experience depressive symptoms [ 16 , 17 ]. On the other hand, managing exacerbated inflammation can alleviate depressive symptoms and slow down the progression of both MDD and its comorbidities [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%